Porous metal plate with multimodal pore structure and preparation method thereof

The porous metal plate with multi-peak pore structure is prepared by mercury intrusion method, which solves the problems of unsuitable pore size and influence of impurity ions in the existing technology, realizes efficient gas-liquid transmission and low contact resistance, and improves the performance and stability of the electrolytic cell.

CN120619356AActive Publication Date: 2025-09-12北京怀柔实验室
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511116172.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2025-09-12
Estimated Expiration
2045-08-11

AI Technical Summary

Technical Problem

Existing porous metal materials have problems in electrolytic cells, such as unsuitable pore size, disordered distribution, and residual impurity ions in the transport layer that affect the life of the electrolytic cell. In addition, existing methods make it difficult to simultaneously improve gas-liquid transmission efficiency and reduce contact resistance.

Method used

The porous metal plate is prepared by mercury intrusion method to form a multi-peak structure with a pore size distribution in the range of 1μm-120μm, including small pores and large pores with a volume ratio of 1:1.5-1:7, which are staggered. The stability and conductivity of the small and large pores are ensured through a sintering process.

Benefits of technology

It achieves the improvement of gas-liquid transmission efficiency, rapid discharge of generated gas, reduced contact resistance, improved catalyst utilization, extended electrolytic cell life, avoids the introduction of impurity elements, and enhances the stability of the transmission layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120619356A_ABST
    Figure CN120619356A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of manufacturing of catalytic devices, and relates to a porous metal plate with a multimodal pore structure, the porosity is 20-80%, a pore size distribution curve obtained by adopting a mercury intrusion method has at least two peaks in a range of 1-120 microns, the two peaks comprise a first peak P1 and a second peak P2, a valley bottom exists between the first peak P1 and the second peak P2, the pore size corresponding to the valley bottom position is X microns, X is between 15 and 40, and the pore size of the porous metal plate is 1-20 microns. A first peak P1 exists in a range of 1 [mu] m to X [mu] m, a second peak P2 exists in a range of more than X [mu] m and less than or equal to 120 [mu] m, the first peak P1 corresponds to a small pore, the second peak P2 corresponds to a large pore, the pore diameter of the small pore is 1 [mu] m to X [mu] m, the pore diameter of the large pore is more than X [mu] m and less than or equal to 120 [mu] m, and the volume ratio of the small pore to the large pore is 1: 1.5-1: 7. The porous metal plate provided by the invention has multi-peak pore structure distribution, is suitable for hydrogen production by electrolyzing water, and can realize efficient transmission of reactants, increase the contact area between the porous metal plate and a catalyst layer, reduce the contact resistance and improve the utilization rate of a catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalytic device manufacturing, and in particular to a porous metal plate with a multi-peak pore structure and a preparation method thereof. Background Art

[0002] Porous metal sintered bodies, obtained by sintering titanium-based, nickel-based, stainless steel, and other metal powders, have long been used as filters. However, in recent years, they have also attracted attention for applications such as substrates for electrode plates for nickel-hydrogen batteries and lithium batteries, biological materials, catalyst substrates, fuel cells, and components of hydrogen production stacks. The porous transport layer is a key component in water electrolysis technology, serving as a conductor, transporting gas and liquid, and providing support within the water electrolysis cell. Currently, it primarily consists of metal fiber felt and powder porous sintered bodies. The pore structure often exhibits a single peak with a predominantly certain size. In the electrolytic cell, gas and liquid are transported in reverse through the transport layer, competing and influencing each other within the pores, thus affecting impedance and transmission efficiency.

[0003] Patent document CN105435305B discloses a porous titanium composite material and its preparation method, which are mainly used to solve the problems of long-term antibacterial properties and promoting the growth of bone cells and tissues. The method forms micropores on the walls of large pores by adding pore-forming agents and anodic oxidation reactions. However, when it is used in an electrolytic cell, the surface oxide layer affects the conductivity and electrolytic performance.

[0004] Patent application with publication number CN1531470A discloses a method for manufacturing a titanium powder sintered body, wherein the method sinters spherical powder of titanium or titanium alloy based on gas atomization method to produce a sintered body with a porosity of 35% to 55%. If used in an electrolytic cell, its pore structure is unimodal.

[0005] Patent application CN1846835A discloses a method for producing titanium powder sintered bodies. This method involves screening the raw materials and performing pressureless sintering, achieving a gradual increase in pore size from one surface to the next. However, using this method in an electrolytic cell increases the thickness of the sintered body without improving performance.

[0006] Patent document CN100457333C discloses a method for preparing a metal porous thin titanium plate. The method comprises placing titanium powder in a mold box and performing vacuum sintering to obtain a sample with a porosity of 45% to 60% and a thickness of 0.2 to 0.8 mm. The sample is used in an electrolytic cell and has a relatively simple pore structure.

[0007] Patent application publication number CN109897984A discloses a method for preparing a titanium-based porous metal material. The method utilizes interconnected pores left at the contact points after the burnout of polystyrene foam microspheres. The material is then expanded and cracked by the decomposition of calcium chloride dihydrate to produce water vapor and hydrogen chloride gas, and the volatilization of the calcium chloride. However, its use in electrolytic cells can easily generate impurity ions, which can shorten the cell's lifespan.

[0008] There are also methods for preparing porous materials with gradient pores, but these often involve discontinuous gradients, which can still increase mass transfer impedance. There are also methods for enhancing gas-liquid transport capabilities through hydrophilic-hydrophobic modification, but the durability of the hydrophilic-hydrophobic properties can be problematic.

[0009] Although some existing patents have achieved different pore size distributions, there are still problems such as the pore size is not suitable for the electrolytic cell, the pore size distribution is disordered, and there are residual impurity ions in the transport layer that affect the life of the electrolytic cell. Summary of the Invention

[0010] In order to at least partially achieve the above-mentioned invention objectives, this application provides the following technical solutions: The present application provides a porous metal plate with a multi-peak pore structure, wherein the porosity of the porous metal plate is 20% to 80%, and the pore size distribution curve obtained by the mercury intrusion method has at least two peaks in the range of 1 μm-120 μm, the two peaks including a first peak P1 and a second peak P2, and a valley exists between the first peak P1 and the second peak P2, and the valley corresponds to a pore size of X μm, wherein X is between 15 and 40, the first peak P1 exists in the range of 1 μm-X μm, and the second peak P2 exists in the range of greater than X μm and less than or equal to 120 μm, the first peak P1 corresponds to small pores, and the second peak P2 corresponds to large pores, the pore size of the small pores is 1 μm-X μm, the pore size of the large pores is greater than X μm and less than or equal to 120 μm, and the volume ratio of the small pores to the large pores is 1:1.5-1:7.

[0011] Preferably, the small holes and the large holes are arranged alternately.

[0012] Preferably, the volume ratio of the small pores to the large pores is 1:1.5-1:6, and the volume ratio can also be specifically 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.5, 1:2.7, 1:3.0, 1:3.2, 1:3.5, 1:4.0, 1:4.5, 1:5.0, 1:5.5, etc.

[0013] Preferably, the intrinsic contact resistance of the porous metal plate is 0.5 to 1.2 mΩ·cm 2@2MPa, the intrinsic contact resistance can be specifically 0.6mΩ·cm 2 @2MPa, 0.7mΩ·cm 2 @2MPa, 0.8mΩ·cm 2 @2MPa, 0.9mΩ·cm 2 @2MPa, 1.0mΩ·cm 2 @2MPa, 1.1mΩ·cm 2 @2MPa, etc.

[0014] Preferably, the porosity of the porous metal plate is 25% to 75%.

[0015] Preferably, the thickness of the porous metal plate is 0.01 to 10 mm, more preferably 0.05 to 5 mm, and can be specifically 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 2 mm, 3 mm, 4 mm, etc.

[0016] Preferably, the porous metal plate is made of titanium, nickel, titanium alloy, nickel alloy or stainless steel.

[0017] Preferably, the titanium alloy is Ti-6Al-4V, Ti-5Al-2.5Sn, Ti-6Al-7Nb, Ti-3Al-2.5V, Ti-2Al-2.5Zr, Ti-8Mn, Ti-6Al-6V-2Sn, Ti-6Al-2Sn-4Zr-6Mo, Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-2Sn-2Zr-2Mo, Ti-3Al- 5Mo-4.5V, Ti-6Al-2Sn-4Zr-2Mo, Ti-5Mo-5V-8Cr-3A1, Ti-13V-11Cr-3Al, Ti-2.25Al-11Sn-5Zr-1Mo-0.2Si, Ti-6Al-2Zr-1Mo-1V, Ti-15V-3Cr-3Sn-3Al or Ti-8Al-1Mo-1V; the nickel alloy is Inconel 600, Inconel 601, Inconel 625, Inconel 690, Inconel 718, Inconel 800, Inconel 825, Inconel 901, Hastelloy B, Hastelloy C, Hastelloy X, Hastelloy R or Hastelloy G.

[0018] The present application also provides a method for preparing a porous metal plate, comprising: A metal fine powder having a particle size D10 of 3 μm to 60 μm and a difference between D10 and D90 of less than 10 μm is mixed with an appropriate amount of a binder to form granules, and the granules are passed through a 60 μm to 150 μm sieve to obtain powder A; The powder A, a coarse metal powder with a particle size D10 of 60 μm to 200 μm and a difference between D10 and D90 of less than 10 μm, and an appropriate amount of a binder are mixed and granulated, and the mixture is passed through a 180 μm to 300 μm sieve to obtain a powder B; The powder B is formed into a metal plate green body, and then subjected to debinding and sintering to obtain the porous metal plate.

[0019] Preferably, the binder is one or more of polyvinyl alcohol, ethanol, stearic acid, zinc stearate, tetrapentaerythritol stearate, ethylene bisstearamide, paraffin wax, microcrystalline wax, carnauba wax, Fischer-Tropsch wax, polyethylene wax, polyoxymethylene, ethylene-vinyl acetate copolymer, polypropylene or polyethylene solution.

[0020] Based on the above technical solution, it can be seen that the porous metal plate and the preparation method of the present application have at least one of the following beneficial effects compared with the existing technology: (1) The porous metal plate of the present application has a multi-peak pore structure with large and small pores, and is used for the transport layer of the electrolytic hydrogen production device, especially the anode transport layer, wherein the small pores are conducive to the transport of water, and the large pores are conducive to the transport of gas. The ratio of large and small pores can achieve efficient transport of reactants, and the generated gas can be quickly discharged. At the same time, the transport layer is located between the anode side plate and the membrane electrode, and is in contact with both the plate and the membrane electrode anode catalyst. The multi-peak structure porous metal plate constructed by this method can increase the contact area, thereby reducing the contact resistance and improving the utilization rate of the catalyst.

[0021] (2) Compared with other preparation processes such as adding pore-forming agents or chemical modification, the present application uses fewer types of raw materials and a simpler preparation method. Impurity elements that affect the life and service stability of the electrolytic cell will not be introduced during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The following is a further description of this application with reference to the accompanying drawings and attached tables: Figure 1 This is a schematic diagram of an electrolytic stack device; Figure 2a 、 2b This is a physical picture of the microstructure of the porous metal plate prepared in Example 1; Figure 2c 、 2d This is a physical picture of the microstructure of commercial titanium felt; Figure 3 is the pore size distribution curve corresponding to the pore size of Example 1; Figure 4 is the cumulative mercury intrusion volume distribution curve corresponding to the pore size in Example 1; Figure 5 is the pore size distribution curve corresponding to the pore size of Example 2; Figure 6 is the cumulative mercury intrusion volume distribution curve corresponding to the pore size in Example 2; Figure 7 is the pore size distribution curve corresponding to the pore size of Example 3; Figure 8 is the cumulative mercury intrusion volume distribution curve corresponding to the pore size in Example 3; Figure 9 is the pore size distribution curve corresponding to the pore size of Example 4; Figure 10 is the cumulative mercury intrusion volume distribution curve corresponding to the pore size in Example 4; Figure 11 is the pore size distribution curve of the corresponding pore size of commercial titanium felt; Figure 12 is the cumulative mercury intrusion volume distribution curve of the corresponding pore size of commercial titanium felt; Figure 13 The single cell test performance comparison of Examples 1-4 and commercial titanium felt is shown; DETAILED DESCRIPTION In order to make the purpose, technical solutions and advantages of this application more clear, this application is further described in detail below in conjunction with specific implementation methods.

[0023] In response to the deficiencies in the prior art, the present application proposes a porous metal plate for having a multi-peak pore structure, wherein the peak of the multi-peak pore refers to the peak on the pore size distribution curve when the mercury intrusion method is used for testing. In the prior art, for example, a unimodal pore refers to a pore size distribution range interval of less than 10 μm, and the pore size distribution curve obtained by the mercury intrusion method has only one peak in the range of 1 μm-120 μm. The porous metal plate provided in the present application has a porosity of 20% to 80%, and the pore size distribution curve obtained by the mercury intrusion method has at least two peaks in the range of 1 μm-120 μm, namely the first peak P1 and the second peak P2, which can be two peaks or more than two peaks, such as three peaks or four peaks. The first peak P1 corresponds to small pores, and the second peak P2 corresponds to large pores. The inventors found that the presence of small pores and large pores in the porous metal plate can solve the above-mentioned technical problems.

[0024] In a preferred embodiment, the pore size distribution curve is preferably 2.5 μm-118.0 μm within the range of 1 μm-120 μm, more preferably 2.9 μm-115.0 μm, and can also be 3.5 μm-113.0 μm, 4.8 μm-112.0 μm, or 5.8 μm-101.0 μm.

[0025] In this application, the mercury intrusion method uses a mercury porosimeter to measure the pore size distribution curve of porous metal plates. This method utilizes the non-wetting properties of mercury on the surfaces of most materials. Increasing pressure forces mercury into the material's internal pores. The greater the external pressure, the smaller the pore radius the mercury can enter. By measuring the amount of mercury entering the pores at different external pressures, the pore volume corresponding to the pore size can be determined.

[0026] In this application, the volume demarcation point between large and small pores is the valley between the first peak P1 and the second peak P2. The valley corresponds to a pore diameter of X μm, where X is between 15 and 40 to ensure a suitable volume ratio of small and large pores.

[0027] In a preferred embodiment, X is preferably between 16 and 38, which can be specifically 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, etc.

[0028] In the present application, the first peak P1 is in the range of 1 μm-X μm, which means that in the cumulative mercury injection volume distribution curve of the corresponding pore size, the pore size value corresponding to the first peak P1 is greater than or equal to 1 μm and less than or equal to X μm, and the second peak P2 is in the range of greater than X μm and less than or equal to 120 μm, which means that in the cumulative mercury injection volume distribution curve of the corresponding pore size, the pore size value corresponding to the second peak P2 is greater than X μm and less than or equal to 120 microns; the pore size of the small pore is 1 μm-X μm, and the pore size of the large pore is greater than X μm and less than or equal to 120 μm.

[0029] In a preferred embodiment, the large pores and the small pores are arranged in a staggered manner. Staggered arrangement means that when observed using a SEM, there are large pores and small pores in the region, and the large pores and the small pores are arranged adjacent to each other.

[0030] The porous metal plate provided in the present application is prepared by a sintering process and is preferably used as a transport layer for hydrogen production by electrolysis of water and a transport layer for fuel cells.

[0031] The electrolysis device described in this application is a water electrolysis hydrogen production device, and its typical structure is a multi-layer stack of components. The transmission layer provided in this application is located between the anode side plate and the membrane electrode, and is in contact with both the plate and the membrane electrode anode catalyst.

[0032] like Figure 1 Figure 1 shows a schematic diagram of a water electrolysis hydrogen production device using a transport layer prepared in this application and commercial titanium felt. In this application, the transport layer makes point contact with the anode, cathode, and membrane electrode, resulting in a large contact area and low contact resistance. In contrast, the commercial titanium felt makes line contact, resulting in a smaller contact area and higher contact resistance.

[0033] In a preferred embodiment, the first peak P1 is distributed in the range of 2μm-28μm, preferably in the range of 3μm-26μm, more preferably in the range of 4μm-25μm, particularly preferably in the range of 5μm-23μm, and most preferably in the range of 6μm-20μm; the second peak P2 is preferably distributed in the range of 32μm-110μm, more preferably in the range of 35μm-100μm, particularly preferably in the range of 40μm-90μm, most preferably in the range of 50μm-70μm, and most preferably in the range of 55μm-65μm.

[0034] In a preferred embodiment, multiple peaks may be distributed in the range of 1-18 μm, for example, two peaks, a third peak may be distributed in the range of 1-10 μm, and a fourth peak may be distributed in the range of 10 μm-18 μm; multiple peaks may be distributed in the range of 30-90 μm, which may be two, three, four, five or more, for example, a fifth peak may be distributed in the range of 30-40 μm, and a sixth peak may be distributed in the range of 80-90 μm.

[0035] In a preferred embodiment, the overall porosity of the porous metal plate is preferably 30% to 70%, more preferably 40% to 60%, and may also be 45%, 50%, 55%, etc.

[0036] In a preferred embodiment, the porous metal plate is made of titanium, nickel, titanium alloy, nickel alloy or stainless steel.

[0037] In a preferred embodiment, the titanium alloy is, for example, Ti-6Al-4V, Ti-5Al-2.5Sn, Ti-6Al-7Nb, Ti-3Al-2.5V, Ti-2Al-2.5Zr, Ti-8Mn, Ti-6Al-6V-2Sn, Ti-6Al-2Sn-4Zr-6Mo, Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-2Sn-2Zr-2Mo, Ti-3Al-5Mo-4.5V, Ti-5Mo-5V-8Cr-3A1, Ti-13V-11Cr-3Al, Ti-2.25Al-11Sn-5Zr-1Mo-0.2Si, Ti-6Al-2Zr-1Mo-1V, Ti-15V-3Cr-3Sn-3Al or Ti-8Al-1Mo-1V; the nickel alloy is, for example, Inconel 600, Inconel 601, Inconel 625, Inconel 690, Inconel 718, Inconel 800, Inconel 825, Inconel 901, Hastelloy B, Hastelloy C, Hastelloy X, Hastelloy R or Hastelloy G, etc.

[0038] The preparation method of the porous metal plate in the present application includes: mixing and granulating a metal fine powder with a particle size D10 of 3μm-60μm and a difference between D10 and D90 within 10μm with an appropriate amount of binder, and passing the mixture through a 60μm-150μm sieve to obtain powder A; mixing and granulating the powder A, a metal coarse powder with a particle size D10 of 60μm-200μm and a difference between D10 and D90 within 10μm, and an appropriate amount of binder, and passing the mixture through a 180μm-300μm sieve to obtain powder B; forming the powder B into a metal plate green body, and then debinding and sintering to obtain the porous metal plate.

[0039] In a preferred embodiment, the particle size D10 of the metal fine powder is 5-50μm, and can also be 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, and 45μm; the particle size D10 of the metal coarse powder is 70-190μm, and can also be 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, etc., and the difference between the particle size D10 and D90 of the above metal powders is within 10μm, specifically 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or 9μm.

[0040] In a preferred embodiment, the mass ratio of the fine metal powder to the coarse metal powder is 1:1-1:5, and can be specifically 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, etc.

[0041] In a preferred embodiment, the metal fine powder is titanium powder, titanium alloy powder, nickel powder, nickel alloy powder or stainless steel powder; the metal coarse powder is titanium powder, titanium alloy powder, nickel powder, nickel alloy powder or stainless steel powder.

[0042] In a preferred embodiment, the binder is one or more of polyvinyl alcohol, ethanol, stearic acid, zinc stearate, tetrapentaerythritol stearate, ethylene bisstearamide, paraffin wax, microcrystalline wax, carnauba wax, Fischer-Tropsch wax, polyethylene wax, polyoxymethylene, ethylene-vinyl acetate copolymer, polypropylene or polyethylene solution.

[0043] In a preferred embodiment, the sieve used to obtain powder A is 70-120 μm, preferably 80-110 μm, 90-100 μm, etc. In a preferred embodiment, the sieve used to obtain powder B is 200-290 μm, and can also be 220-280 μm, 230-270 μm, 240-260 μm, etc.

[0044] In a preferred embodiment, granulation can be carried out by stirring in a mortar, crucible, ribbon mixer, plowshare mixer, spiral cone mixer or the like; stirring can be carried out in a single direction or alternately in different directions, preferably in a single direction; spray granulation can also be used, and there is no particular limitation in this application.

[0045] In a preferred embodiment, when the powder B is formed into a metal plate green body, a doctor blade method, a dip coating method, a die coating method, a rod coating method, a screen printing method, an offset printing method, a gravure printing method, an inkjet method, a spray coating method, a dispensing method, a spin coating method, a tape casting method, etc. can be used.

[0046] In a preferred embodiment, the debinding is carried out in a sintering device at a temperature of 0.1-50°C / min, preferably 0.5-30°C / min, more preferably 0.8-10°C / min, and most preferably 1-5°C / min, and kept at 350-700°C, preferably 400-600°C for 0.5-3h, preferably 0.5-2h, and more preferably 1-1.5h.

[0047] In a preferred embodiment, after debinding, the sintering is carried out in an inert atmosphere or vacuum environment at a rate of 0.1-50°C / min, preferably 0.5-30°C / min, more preferably 0.8-10°C / min, and most preferably 1-5°C / min, and is kept at 800-1200°C, preferably 850-1100°C, and most preferably 900-1000°C for 0.5-3h, preferably 0.5-2h, more preferably 1-1.5h, and then cooled naturally. In a preferred embodiment, the sintering can be performed by pressureless sintering, hot pressing sintering, tape casting sintering, or rolling sintering.

[0048] According to the present application, after metal fine powder and metal coarse powder of different particle sizes are used to granulate and form blanks, during the sintering process, the metal fine powder and metal coarse powder have different sintering dynamics due to the size difference. The large-sized particles form a porous skeleton, the contact area between the particles is small, the atomic diffusion path is long in the early stage of sintering, and it is difficult to form a continuous metallurgical bond. During the sintering process, only local necking is formed by surface atomic diffusion, and the particle gaps cannot be completely closed, and finally large pores of more than 30 μm are retained; the small-sized particles fill the gaps between the large-sized particles, the contact area between the particles is large, the atomic diffusion distance is short, and the sintering neck is quickly formed and expanded. Development, at the same temperature it is easier to reach the densification conditions, forming dense areas and leaving isolated small pores, causing the pores between particles to shrink to less than 30μm; from a thermodynamic point of view, the system tends to reduce the surface energy, and the large pores shrink first due to their large volume and high surface energy, but the binding force between large-sized particles is weak, and the shrinkage is hindered, resulting in the retention of large pores, while the small pores are not easy to close due to their low surface energy and high stability; from a kinetic point of view, the sintering of large-sized particles requires higher activation energy, and the diffusion rate is low at low temperatures, making it impossible to effectively densify, while the diffusion rate of small-sized particles is fast, and a small pore structure is quickly formed in the early stage of sintering. In summary, the meticulous design of the preparation process from raw material processing to sintering makes the porous metal plate prepared in this application have unique multi-peak pore structure characteristics when tested using the mercury intrusion method.

[0049] The test data in this application was obtained using the following test method: The pore size distribution and porosity of metal plates were measured using mercury intrusion in accordance with the requirements of "GB / T 21650.1-2008: Determination of Porosity and Pore Size Distribution of Solid Materials by Mercury Intrusion and Gas Adsorption Methods - Part 1: Mercury Intrusion Method," using a fully automated mercury intrusion porosimeter. The calculation method used in this application uses a mercury intrusion starting point of 101.0 μm (the first measurement point for mercury intrusion below 120.0 μm; pores larger than 120.0 μm are due to errors introduced by the test sample edge). The mercury intrusion endpoint is the maximum cumulative mercury intrusion (the first measurement point at which the cumulative mercury intrusion value becomes constant). The principle of mercury intrusion porosimetry pore size distribution testing utilizes the non-wetting properties of mercury on the surface of most materials. Increasing pressure forces mercury into the material's pores. The greater the external pressure, the smaller the pore radius that mercury can enter. Measuring the amount of mercury entering the pores at different external pressures provides the pore volume corresponding to the pore size. The dividing point between the volume of large and small pores is the "valley" between the two peaks.

[0050] Since the amount of mercury injected is controlled by hydraulic pressure and the sensor accuracy is 0.1~0.2% of the full scale, the aperture corresponding to the test result is discontinuous. The measurable points of this application include 2.5μm, 2.9μm, 3.5μm, 4.8μm, 5.4μm, 5.6μm, 6.0μm, 6.6μm, 7.2μm, 8.1μm, 9.1μm, 10.1μm, 11.3μm, 12.5μm, 14.0μm, 15.5μm, 17.3μm, 19.1μm, 21.4μm, and 24.2μm. , 26.0μm, 27.9μm, 30.3μm, 36.4μm, 45.5μm, 52.0μm, 60.7μm, 72.8μm, 90.3μm, 101.0μm, 120.7μm and other data points. After a large number of experiments, it was confirmed that the multi-peak pore size of the porous metal plate prepared in the present application has a first peak P1 at 1-Xμm and a second peak P2 at greater than Xμm-120.0μm. The volume of pores smaller than 1μm can be ignored, and the pores larger than 120μm are the errors caused by the edge of the test sample.

[0051] The powder particle size is tested using a laser particle size analyzer. Based on the scattering and diffraction phenomena produced by the interaction between laser and particles, the laser particle size analyzer determines the particle size and distribution by analyzing the spatial distribution of scattered light. The core of the test is to measure the intensity of scattered light at different angles, combine it with Mie scattering theory or Fraunhofer diffraction theory for mathematical inversion, and finally obtain the particle size distribution data.

[0052] The contact resistance test was conducted using a four-probe method with a bipolar plate four-probe resistance tester. The single cell performance test was conducted using a commercial PEM water electrolysis test fixture with an active area of ​​25 cm. 2 , temperature 60°C, during the test, only the porous metal plate prepared in this application and the commercial titanium felt were replaced, and the other accessories remained the same.

[0053] Below, in conjunction with specific embodiment, the preparation method of the porous metal plate of the present application is further elaborated, and those skilled in the art can refer to the content of the present application and appropriately improve the process parameters to realize. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included within the scope of the present application. The method and application of the present application have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the method and application described in the present application without departing from the content, spirit and scope of the present application to realize and apply the technology of the present application.

[0054] Example 1 (1) Prepare fine titanium powder with D10 of 30 μm and D90 of 40 μm and coarse titanium powder with D10 of 50 μm and D90 of 60 μm; (2) Pour fine titanium powder into a mortar, then add an appropriate amount of 5% PVA aqueous solution, and gently stir in one direction with the mortar until the fine powder sticks together and forms granules. Pass through a 90 μm sieve to obtain powder A; (3) Powder A and coarse titanium powder were placed in a mortar at a mass ratio of 1:4.5, and then an appropriate amount of 5% PVA aqueous solution was poured in. The mixture was gently stirred in one direction with the mortar until the coarse powder and powder A were bonded together and formed into granules. The mixture was passed through a 210 μm sieve to obtain powder B. (4) Then pour an appropriate amount of powder B into the mold, scrape it flat with a scraper, and then place it in the furnace. Heat it at a rate of 3°C / min and keep it at 550°C for 1 hour to debind. Then continue to heat it at a rate of 3°C / min and keep it at a sintering temperature of 1000°C for 2 hours. Then cool it naturally to obtain a metal plate.

[0055] The SEM observation results of the metal plate are as follows Figure 2a 、 Figure 2b As shown, it can be clearly seen that the large pores and small pores are arranged roughly alternately, that is, the large pores and small pores are arranged adjacent to each other. After the pore size is tested by mercury intrusion method, the pore size distribution curve of the corresponding pore size is obtained as shown in Figure 3 As shown, the cumulative mercury volume distribution curve of the corresponding pore size is obtained as follows Figure 4 shown.

[0056] from Figure 3 It can be seen that there are two peaks in the range of about 5.4μm to 101.0μm. The first peak P1 is located at 24.2μm; the second peak P2 is located at 51.9μm, and the "valley bottom" between the two peaks is located at 30.3μm. Figure 4 It can be seen that the cumulative mercury injection volume corresponding to the pore size of 101.0μm is 0.048mL / g, the cumulative mercury injection volume corresponding to the pore size of 30.3μm is 0.281mL / g, and the cumulative mercury injection volume corresponding to the pore size of 5.4μm is 0.438mL / g. Figure 4 The test results show that the pore distribution is between 5.4μm and 101.0μm, among which the volume of small pores between 5.4-30.3μm is 0.157 mL / g, and the volume of large pores between 30.3-101.0μm is 0.233 mL / g. It can be obtained that the volume of small pores accounts for 40% and the volume of large pores accounts for 60%.

[0057] The contact resistance of the porous metal plate was tested and listed in Table 1. The contact resistance of Example 1 was measured to be 1.1 mΩ·cm 2 @2MPa, with good electrical conductivity.

[0058] Example 2 (1) Prepare fine titanium powder with D10 of 20 μm and D90 of 30 μm and coarse titanium powder with D10 of 80 μm and D90 of 90 μm; (2) Pour fine titanium powder into a mortar, then add an appropriate amount of 5% PVA aqueous solution, and gently stir in one direction with the mortar until the fine powder sticks together and forms granules. Pass through a 120 μm diameter sieve to obtain powder A; (3) Powder A and coarse titanium powder were placed in a mortar at a mass ratio of 1:3.5, and then an appropriate amount of 5% PVA aqueous solution was poured in. The mixture was gently stirred in one direction with the mortar until the coarse powder and powder A were bonded together and formed into granules. The granules were passed through a 280 μm diameter sieve to obtain powder B. (4) Then pour an appropriate amount of powder B into the mold, scrape it flat with a scraper, and then place it in the furnace. Heat it at a rate of 3°C / min and keep it at 550°C for 1 hour to debind. Then continue to heat it at a rate of 3°C / min, keep it at a sintering temperature of 1000°C for 1 hour, and then cool it naturally to obtain a metal plate.

[0059] The metal plate prepared in Example 2 was tested for pore size using mercury intrusion porosimetry to obtain a pore size distribution curve corresponding to the pore size. Figure 5 As shown, the cumulative mercury volume distribution curve of the corresponding pore size is obtained as follows Figure 6 As shown. Figure 5 It can be seen that there are two peaks in the range of about 2.5μm to 101.0μm. The first peak P1 is located at 6.0μm, the second peak P2 is located at 45.4μm, and the "valley bottom" between the two peaks is located at 19.1μm. Figure 6 It can be seen that the cumulative mercury injection volume corresponding to the pore size of 101.0μm is 0.022mL / g, the cumulative mercury injection volume corresponding to the pore size of 19.1μm is 0.361mL / g, and the cumulative mercury injection volume corresponding to the pore size of 2.5μm is 0.411mL / g. Figure 6 The test results show that the pore distribution is between 2.5μm and 101.0μm, among which the volume of small pores between 2.5-19.1μm is 0.050 mL / g, and the volume of large pores between 19.1-101.0μm is 0.339 mL / g. It can be obtained that the volume of small pores accounts for 13% and the volume of large pores accounts for 87%.

[0060] The contact resistance of the porous metal plate was tested and listed in Table 1. The contact resistance of Example 2 was measured to be 0.8 mΩ·cm 2 @2MPa, with good electrical conductivity.

[0061] Example 3 A method for preparing a porous metal plate having a multi-peak pore structure, the method comprising the following steps: (1) Prepare fine titanium powder with D10 of 20 μm and D90 of 30 μm and coarse titanium powder with D10 of 80 μm and D90 of 90 μm; (2) Pour fine titanium powder into a mortar, then pour in an appropriate amount of 5% PVA aqueous solution, and gently stir in one direction with the mortar until the fine powder sticks together and forms granules. Pass through a 60 μm diameter sieve to obtain powder A; (3) Powder A and coarse titanium powder were placed in a mortar at a mass ratio of 1:4.5, and then an appropriate amount of 5% PVA aqueous solution was poured in. The mixture was gently stirred in one direction with the mortar until the coarse powder and powder A were bonded together and formed into granules. The granules were then passed through a 200 μm diameter sieve to obtain powder B. (4) Then pour an appropriate amount of powder B into the mold, scrape it flat with a scraper, and then place it in the furnace. Heat it at a rate of 3°C / min and keep it at 550°C for 1 hour to debind. Then continue to heat it at a rate of 3°C / min, keep it at a sintering temperature of 1000°C for 1 hour, and then cool it naturally to obtain the final product.

[0062] The metal plate prepared in Example 3 was tested for pore size using mercury intrusion porosimetry to obtain a pore size distribution curve corresponding to the pore size. Figure 7 As shown, the cumulative mercury volume distribution curve of the corresponding pore size is obtained as follows Figure 8 As shown. Figure 7 It can be seen that there are two peaks in the range of about 3.9μm to 101.0μm. The first peak P1 is located at 10.1μm, the second peak P2 is located at 60.7μm, and the "valley bottom" between the two peaks is located at 24.1μm. Figure 8 It can be seen that the cumulative mercury injection volume corresponding to the pore size of 101.0μm is 0.022mL / g, the cumulative mercury injection volume corresponding to the pore size of 24.1μm is 0.180mL / g, and the cumulative mercury injection volume corresponding to the pore size of 3.9μm is 0.247mL / g. Figure 8 The test results show that the pore distribution is between 3.9 μm and 101.0 μm, of which the volume of small pores between 3.9 and 24.1 μm is 0.067 mL / g, and the volume of large pores between 24.1 and 101.0 μm is 0.158 mL / g. The volume of small pores accounts for 30% and the volume of large pores accounts for 70%. The contact resistance of the porous metal plate is tested and listed in Table 1. The contact resistance of Example 3 was measured to be 0.6 mΩ·cm 2 @2MPa, with good electrical conductivity.

[0063] Example 4 A method for preparing a porous metal plate having a multi-peak pore structure, the method comprising the following steps: (1) Prepare fine titanium powder with D10 of 10 μm and D90 of 20 μm and coarse titanium powder with D10 of 80 μm and D90 of 90 μm; (2) Pour fine titanium powder into a mortar, then pour in an appropriate amount of 5% PVA aqueous solution, gently stir in one direction with the mortar to obtain a uniformly mixed slurry, and use spray granulation technology to obtain powder A; (3) Powder A and coarse titanium powder were mixed uniformly in a mass ratio of 1:4.5 to obtain powder B; (4) Then pour an appropriate amount of powder B into the mold, dry press it into shape, and then place it in a furnace. Heat it at a rate of 3°C / min and keep it at 550°C for 1 hour to debind. Then continue to heat it at a rate of 3°C / min and keep it at a sintering temperature of 1000°C for 1 hour. Then cool it naturally to obtain the final product.

[0064] The metal plate prepared in Example 4 was tested for pore size using mercury intrusion method to obtain the pore size distribution curve of the corresponding pore size. Figure 9 As shown, the cumulative mercury volume distribution curve of the corresponding pore size is obtained as follows Figure 10 As shown. Figure 9 It can be seen that there are two peaks in the range of about 2.9μm to 101.0μm. The first peak P1 is located at 18.1μm, the second peak P2 is located at 52.0μm, and the "valley bottom" between the two peaks is located at 30.3μm. Figure 10 It can be seen that the cumulative mercury injection volume corresponding to the pore size of 101.0μm is 0.019mL / g, the cumulative mercury injection volume corresponding to the pore size of 30.3μm is 0.169mL / g, and the cumulative mercury injection volume corresponding to the pore size of 3.8μm is 0.250mL / g. Figure 10 The test results show that the pore distribution is between 3.8 μm and 101.0 μm, of which the volume of small pores between 3.8 and 30.3 μm is 0.081 mL / g, and the volume of large pores between 30.3 and 101.0 μm is 0.150 mL / g. The volume of small pores accounts for 35% and the volume of large pores accounts for 65%. The contact resistance of the porous metal plate is tested and listed in Table 1. The contact resistance of Example 4 was measured to be 0.5 mΩ·cm 2 @2MPa, with good electrical conductivity.

[0065] For comparison, commercial titanium felt (Bekaert-2GDL10-0.25) was tested using mercury intrusion method to measure pore size. The microstructure is shown in the figure below. Figure 2c and Figure 2d As shown, the pore size distribution curve of the corresponding pore size is obtained as shown in Figure 11 As shown, there is only one peak, and the cumulative mercury volume distribution curve of the corresponding pore size is obtained as follows Figure 12 shown.

[0066] The contact resistance and single cell performance tests were performed on Examples 1-4 and commercial titanium felt, and the results are shown in Tables 1 and Figure 13 As shown in the figure, it can be seen that the contact resistance of the porous metal plate prepared in this application is better than that of the commercial titanium felt, and the single cell test performance is better than that of the commercial titanium felt. 2 The performance at current density is 4-11mV better than that of commercial titanium felt.

[0067] Table 1 Test results of examples and commercial titanium felt

[0068] When used in a PEM water electrolysis device, the porous metal plate provided in this application, with its multi-peak pore structure, can optimize the gas-liquid transport process during the reaction and improve contact with the bipolar plate and membrane electrode, thereby enhancing the performance and stability of water electrolysis. Specifically, the gas encounters less flow resistance in the large pores with low curvature, allowing the gas to quickly discharge from the anode, reducing bubble coverage on the electrode surface and preventing blockage of reactive sites. This can reduce concentration polarization and increase the reaction rate. Therefore, larger pore sizes promote gas-liquid transport and separation, which is beneficial to the electrochemical reaction of water electrolysis. However, this reduces the contact area between the transport layer and the membrane electrode, thereby increasing contact resistance and hindering the electrochemical reaction of PEM water electrolysis. The small pores generate high capillary pressure to actively "draw" liquid water to the catalyst layer-membrane interface, ensuring full hydration of the proton exchange membrane (PEM) and maintaining high proton conductivity. At the same time, the small pore area forms a dense micro-bump structure, increasing the microscopic contact points between the PTL and the catalyst layer, thereby reducing contact resistance.

[0069] The multi-peak pore structure solves three major contradictions at the same time through the spatial division of labor of large pores for gas conduction and small pores for liquid conduction, as well as the synergistic mechanism of small pores enhancing interfacial contact: large pores for low-resistance exhaust and small pores for capillary water supply can optimize the conflict between gas and liquid transmission; large pores guarantee gas channels and small pores increase the contact point density to optimize the interfacial resistance and mass transfer balance; multiple pore structures work together to maintain uniform water / heat distribution to improve the stability of the water electrolysis reaction.

[0070] The above is only a preferred embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.

Claims

1. A porous metal plate having a multi-peak pore structure, characterized in that: The porosity of the porous metal plate is 20% to 80%, and the pore size distribution curve obtained by the mercury intrusion method has at least two peaks in the range of 1μm-120μm, the two peaks including a first peak P1 and a second peak P2, a valley exists between the first peak P1 and the second peak P2, and the valley corresponds to a pore size of Xμm, wherein X is between 15 and 40, the first peak P1 exists in the range of 1μm-Xμm, and the second peak P2 exists in the range of greater than Xμm and less than or equal to 120μm, the first peak P1 corresponds to small pores, and the second peak P2 corresponds to large pores, the pore size of the small pores is 1μm-Xμm, the pore size of the large pores is greater than Xμm and less than or equal to 120μm, and the volume ratio of the small pores to the large pores is 1:1.5-1:

7.

2. The porous metal plate according to claim 1, wherein The small holes and the large holes are arranged alternately.

3. The porous metal plate according to claim 2, characterized in that The volume ratio of the small pores to the large pores is 1:1.5-1:

6.

4. The porous metal plate according to claim 3, characterized in that The volume ratio of the small pores to the large pores is 1:2-1:

5.

5. The porous metal plate according to claim 4, characterized in that The intrinsic contact resistance of the porous metal plate is 0.5 to 1.2 mΩ·cm 2 @2MPa.

6. The porous metal plate according to claim 5, characterized in that The porous metal plate is made of titanium, nickel, titanium alloy, nickel alloy or stainless steel.

7. The porous metal plate according to claim 6, characterized in that The porosity of the porous metal plate is 25% to 75%.

8. The porous metal plate according to claim 6, characterized in that The titanium alloys are Ti-6Al-4V, Ti-5Al-2.5Sn, Ti-6Al-7Nb, Ti-3Al-2.5V, Ti-2Al-2.5Zr, Ti-8Mn, Ti-6 Al-6V-2Sn, Ti-6Al-2Sn-4Zr-6Mo, Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-2Sn-2Zr-2Mo, Ti-3Al-5M o-4.5V, Ti-6Al-2Sn-4Zr-2Mo, Ti-5Mo-5V-8Cr-3A1, Ti-13V-11Cr-3Al, Ti-2.25Al-11Sn-5Zr-1Mo-0.2Si, Ti-6Al-2Zr-1Mo-1V, Ti-15V-3Cr-3Sn-3Al or Ti-8Al-1Mo-1V; the nickel alloy is Inconel 600, Inconel 601, Inconel 625, Inconel 690, Inconel 718, Inconel 800, Inconel 825, Inconel 901, Hastelloy B, Hastelloy C, Hastelloy X, Hastelloy R or Hastelloy G.

9. A method for preparing a porous metal plate according to any one of claims 1 to 8, characterized in that: The preparation method comprises: A metal fine powder having a particle size D10 of 3 μm to 60 μm and a difference between D10 and D90 of less than 10 μm is mixed with an appropriate amount of a binder to form granules, and the granules are passed through a 60 μm to 150 μm sieve to obtain powder A; The powder A, a coarse metal powder with a particle size D10 of 60 μm to 200 μm and a difference between D10 and D90 of less than 10 μm, and an appropriate amount of a binder are mixed and granulated, and the mixture is passed through a 180 μm to 300 μm sieve to obtain a powder B; The powder B is formed into a metal plate green body, and then subjected to debinding and sintering to obtain the porous metal plate.

10. The method for preparing a porous metal plate according to claim 9, wherein: The binder is one or more of polyvinyl alcohol, ethanol, stearic acid, zinc stearate, tetrapentaerythritol stearate, ethylene bisstearamide, paraffin wax, microcrystalline wax, carnauba wax, Fischer-Tropsch wax, polyethylene wax, polyoxymethylene, ethylene-vinyl acetate copolymer, polypropylene or polyethylene solution.

Citation Information

Patent Citations

  • Method of producing porous metal thin titanium board

    CN100457333C

  • A porous titanium composite material and its preparation method

    CN105435305B

  • Preparation method of titanium-based metal porous material

    CN109897984A

  • Titanium powder sintered compact

    CN1531470A

  • Titanium powder sintered compact

    CN1846835A